Kelvin Probe Force Microscopy, Current Mapping, and Optical Properties of Hybrid ZnO Nanorods/Ag Nanoparticles - Ishaq Musa (Surfaces)
The optical characteristics and electrical behavior of zinc oxide nanorods (ZnO-NRs) and silver nanoparticles (Ag-NPs) were investigated using advanced scanning probe microscopy techniques. The study revealed that the ZnO nanorods had a length of about 350 nm, while the Ag nanoparticles were spherical with heights ranging from 5 to 14 nm. Measurements with Kelvin probe force microscopy (KPFM) showed that the work functions of ZnO nanorods were approximately 4.55 eV, higher than that of bulk ZnO, and the work function of Ag nanoparticles ranged from 4.54 to 4.56 eV. The electrical characterization of ZnO nanorods, silver nanoparticles, and their hybrid was also conducted using conductive atomic force microscopy (C-AFM) to determine the local current-voltage (I-V) characteristics, which revealed a characteristic similar to that of a Schottky diode. The current-voltage characteristic curves of ZnO nanorods and Ag nanoparticles both showed an increase in current at around 1 V, and the hybrid ZnONRs/AgNP exhibited an increase in turn-on voltage at around 2.5 volts. This suggested that the presence of Ag nanoparticles enhanced the electrical properties of ZnO nanorods, improving the charge carrier mobility and conduction mechanisms through a Schottky junction. The investigation also explored the optical properties of ZnO-NRs, AgNPs, and their hybrid, revealing absorption bands at 3.11 eV and 3.18 eV for ZnO-NRs and AgNPs, respectively. The hybrid material showed absorption at 3.13 eV, indicating enhanced absorption, and the presence of AgNP affected the optical properties of ZnO-NR, resulting in increased photoluminescence intensity and slightly changes in peak positions.